COMPLEX ASSESSMENT OF COMPUTED TOMOGRAPHY OF THE LUNGS AND CLINICAL DATA IN COVID-19 PATIENTS, HOSPITALIZED IN THE CLINIC IN NUR-SULTAN - Rakhimzhanova R.I.; Pavalkis D.; Benberin V.; Dautov T.B.; Abdrakhmanova Zh.S.; Yelshibayeva E.S. (Academic Journal of Physical and Chemical Sciences, 2020)
The ambiguity of the X-ray picture and clinic in patients with coronavirus infection (CVI) was the reason for this analysis in order to avoid diagnostic errors and to achieve the effect of the treatment. Conducted a comparative description of three clinical cases of patients with coronavirus infection COVID-19. All three patients differed in different parameters of SARS Co-2 PCR. In the first two patients who underwent CT on the 7th and 10th days from the onset of the disease on control CT after treatment, a regressive positive dynamics was observed; in the third patient, after an early CT scan on the second day of illness and on the next CT scan performed on the 10th day after the appearance of the clinic and a positive PCR test, progression of signs of viral pneumonia was observed with an increase in the affected area. Thus, the earlier CT was performed, the less pronounced the changes in the CT picture (the lesion volume is up to 5% or no changes are detected). When performing CT scan, patients with a long-term clinic (7-10 days from the onset of the disease) showed a characteristic picture of lung damage - up to 25-30%. The analysis of CT scans performed in the described clinical cases at different times from the onset of the disease, regardless of the results of PCR, confirms the need for CT scans 5-7 days after the first clinical signs appear. Also, as a result of our work, we once again received confirmation from numerous studies conducted in the world on the absence of a correlation between SARS Co-2 PCR and CT data.